The impact of xenophobia on foreign language learning anxiety among Turkish University students: The case of Arabic - Alhourani, Mohammad Issa; Abazoglu, Muhammet; Adel, Mohammed A. Abou; Mahamed, Ahmad M. Al; Abouelnour, Moustafa Mohamed (Research Journal in Advanced Humanities, 2026)
This study examined the relationship between xenophobia and foreign language classroom anxiety among Turkish university students studying Arabic. Using a correlational survey design, data were collected from 655 participants from Arabic Language and Literature, Arabic Translation and Interpreting, and Theology/Preparatory programs. The Foreign Language Classroom Anxiety Scale and Xenophobia Scale were used with a demographic questionnaire. Results showed that female students experienced higher levels of speaking and classroom anxiety than males. Younger students (20–25) reported greater anxiety and xenophobic attitudes, while those aged 31–40 showed more interest in Arabic. Native Turkish speakers had higher anxiety and xenophobia than Kurdish and Arabic speakers. Students in Theology and Preparatory programs reported greater anxiety and xenophobia than Arabic-focused departments. Overall, xenophobia emerged as a psychological and sociocultural barrier to language learning, highlighting the need for inclusive and culturally responsive approaches that foster engagement and reduce anxiety in Arabic education.